Fighting Westway: Environmental Law, Citizen Activism, and the Regulatory War That Transformed New York City - William W. Buzbee (Cornell University Press, 2014)
FROM 1971 TO 1985, battles raged over Westway, a 4.2-mile, multibillion-dollar highway, development, and park project proposed for placement in the Hudson River, in New York City. Th is project was, on a per-mile basis, the most expensive highway ever proposed. Federal interstate funding would have fl owed into a fi nancially struggling New York City. By utilizing new landfi ll in the Hudson, extending at times almost a thousand feet out, Westway would have destroyed dozens of piers and the waters between them. It also, however, would have created new land for development, made many adjacent properties skyrocket in value, and created space for a new river-edge park atop tunneled portions of the highway. In Mayor Ed Kochâ€™s words, the project could have been an â€œenormous economic lift to the city [since] 90 percent would be paid by the federal government, including all infl ationary aspects, so the city was protected.â€ 1 As one Army Corps of Engineers regulator who worked on Westway later refl ected, â€œI think the original planners were clever enoughâ€ to ask, â€œ â€˜How can we get as much federal money as possible to redevelop this area?â€™ â€ 2 It paid to think big. Powerful business and civic leaders like David Rockefeller called it a transformative project supported by the â€œpast three Presidents of the United States, the past four Governors of New York State and every mayor of New York City since John Lindsay.â€ 3 Th e editorial boards of the New York Times and the Daily News and many business and labor leaders also backed Westway. So did New Yorkâ€™s two United States senators.